If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 2x = -1(4 + -3x) -2 + 2x = (4 * -1 + -3x * -1) -2 + 2x = (-4 + 3x) Solving -2 + 2x = -4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 2x + -3x = -4 + 3x + -3x Combine like terms: 2x + -3x = -1x -2 + -1x = -4 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + -1x = -4 + 0 -2 + -1x = -4 Add '2' to each side of the equation. -2 + 2 + -1x = -4 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -4 + 2 -1x = -4 + 2 Combine like terms: -4 + 2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 12(7m+2)=6(4m-7) | | -2(n-1)=10-n | | 20f+14=13f+35 | | 3(5x-3)=51 | | 3G-6g(g-8)=42 | | 4x+5-3=5x-3x+12 | | 4x+1-6x+3+2= | | -6a-34=-5(1+7a) | | 4(r-3)=2(r+8) | | 3x-5=9x-17 | | q=11200-100p-1960 | | 3a+2=a+7 | | -2Ax^2+2Ax+2A-2Bx+b-2C=x^2 | | 27-w=14 | | x=15*90 | | 2s+2=134 | | 6x+9x-22=66-7 | | 5(3x-9)-8=5(x-3)+32 | | (2x-5)(2x-4)=0 | | q=9240-100p | | F(1)=2x-4 | | 10p^2-13p+5=0 | | -4.7v-44.2=-8.3v | | v=523.6*.75 | | 2x-18=-x+24 | | 5x+4x=-9 | | 12-9y-45=-1+y | | -3(8-8x)=-3(x+8) | | v=523.6*(3/4) | | 3(8-2x)=-3+3x | | z^2-11z-12=0 | | 12y-7y+2=5 |